2022
DOI: 10.3934/environsci.2022001
|View full text |Cite
|
Sign up to set email alerts
|

Floating cage aquaculture production in Indonesia: Assessment of opportunities and challenges in Lake Maninjau

Abstract: <abstract> <p>Aquaculture in floating cages in Lake Maninjau has recorded significant growth, even as the largest contributor to total annual aquacultural production in West Sumatra Province. In this study, we assessed the output of floating net cages in Lake Maninjau, Indonesia. We analyzed the characteristics of fish farming, fish fry, feed supply, and production, and the challenges and opportunities for increasing aquacultural production in the future. We used purposive sampling in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Keuntungan lain memelihara ikan lele ukuran rata-rata 10 cm adalah pertumbuhannya lebih cepat dan pakan yang digunakan selama pemeliharaan lebih sedikit ″kalah diharga membeli benih, tetapi menang pada penggunaan pakan″. Bahwa biaya operasional yang paling tinggi untuk budidaya ikan adalah pada pakan yaitu sekitar 70% dari seluruh biaya tidak tetap [16,17,18,19,20,21,22].…”
Section: Penyediaan Benih Ikan Lele Dumbo Dan Proses Budidayaunclassified
“…Keuntungan lain memelihara ikan lele ukuran rata-rata 10 cm adalah pertumbuhannya lebih cepat dan pakan yang digunakan selama pemeliharaan lebih sedikit ″kalah diharga membeli benih, tetapi menang pada penggunaan pakan″. Bahwa biaya operasional yang paling tinggi untuk budidaya ikan adalah pada pakan yaitu sekitar 70% dari seluruh biaya tidak tetap [16,17,18,19,20,21,22].…”
Section: Penyediaan Benih Ikan Lele Dumbo Dan Proses Budidayaunclassified
“…Commercial feed supplemented with different formulated products with the dosage of 150 ml/kg of feed significantly affects the proximate composition of diets. One-way ANOVA results showed a marginal interaction among treatments in the case of protein content (F (3,8) = 1.522, P = 0.282), fat (F (3,8) = 5.663, P = 0.022), carbohydrates (F (3,8) = 1.862, P = 0.214), crude fibre (F (3,8) = 1.445, P = 0.300), and ash (F (3,8) = 0.272, P = 0.844), and the total energy content (F (3,8) =1.112, P = 0.400) differed considerably (P < 0.05) among the four diets (Table 1). Duncan's Post-hoc test revealed that the protein content (21.6967 AE 0.17%) was significantly higher (P < 0.05) in the KP3 diet than in the other treatments, while the carbohydrate (31.19 AE 0.38%), crude fibre (2.82 AE 0.06%), and ash (6.57 AE 0.04%) contents were significantly higher (P < 0.05) in the KP3 diet than in the other diets.…”
Section: Proximate and Amino Acid Profiles Of The Dietsmentioning
confidence: 99%
“…[2][3][4][5] At the same time, for aquaculture operations, the cost of aquafeed is still a significant challenge. 2,[6][7][8] On the other hand, commercial feed produced by factories still does not contain complete nutrition for fish growth, while being acknowledged for its positive effects on food safety. [9][10][11] In this context, enriching fish feed with cost-effective natural ingredient resources is key to increasing feed nutrient quality and feed efficiency in commercial fish farming and ensuring the sustainability of aquaculture operations.…”
Section: Introductionmentioning
confidence: 99%